Puerto Rican Identity, Political Development, and Democracy in New York, 1960-1990 - Cruz, José E., 1953- (Lexington Books, 2017)
This book studies Puerto Ricans in New York City, focusing on political elites, to explore the role of ethnic identity in the maintenance and development of urban democracy. It suggests that ethnic identity structures political participation in ways that challenge and affirm liberal democracy and, thus, is a positive force in political development.